Strategic solutions for sustainable environmental management - Turdiyeva Nigora; Babanazarova Maftuna; Raximova Nargiza; Shoyeva Yulduz (BIO Web of Conferences)
In this article, the impact of ecology on the environment and the impact of its waste on it are studied, and the possibilities of planning this process are studied. In this regard, issues of implementing the relationship between man and nature through the impact of waste on the environment, reducing the impact of electronic waste, further strengthening the impact of ecology on the tourism sector, strategic planning and monitoring of effective environmental management. discussed. Also, the impact of waste on the environment was considered on the basis of various analyses, proposals and recommendations were developed based on the opinions of research scientists.